May Antitransglutaminase Levels Predict Severity of Duodenal Lesions in Adults with Celiac Disease? - Giuseppe Losurdo; Milena Di Leo; Edoardo Santamato; Antonio Giangaspero; Maria Rendina; Carmelo Luigiano; Enzo Ierardi; Alfredo Di Leo (Medicina, 2021)
Background and Objective: Pediatric guidelines on celiac disease (CD) state that children with anti-transglutaminase antibodies (TGAs) >×10 upper limit of normal (ULN) may avoid endoscopy and biopsy. We aimed to evaluate whether these criteria may be suitable for villous atrophy diagnosis in CD adults. Materials and Methods: We retrospectively enrolled patients with CD aged >18 years. TGAs were expressed as xULN. Duodenal lesions were classified as atrophic or non-atrophic according to Marsh-Oberhuber. Fisher’s exact and t-test were used for variables comparison. Receiver operating characteristics (ROC) curve analysis was performed with estimation of area under the curve (AUC), sensitivity, specificity, and positive and negative predictive value (PPV/NPV). Results: One hundred and twenty-one patients were recruited. Sixty patients (49.6%) had TGA >×10 ULN, and 93 (76.8%) had villous atrophy. The cut-off of >×10 ULN had sensitivity = 53.7%, specificity = 64.3%, PPV = 83.3%, and NPV = 29.5% to predict atrophy. Therefore, considering pediatric criteria, in 50 (41.3%) patients, biopsy could have been avoided. Patient subgroup with atrophy had higher TGA levels despite being not significant (37.2 ± 15.3 vs. 8.0 ± 1.3 ULN, p = 0.06). In adults, a slightly better diagnostic performance was obtained using a cut-off of TGA >×6.2 ULN (sensitivity = 57.1%, specificity = 65.6%, and AUC = 0.62). Conclusions: Despite our confirmation that villous atrophy is linked to high TGA levels, CD and atrophy diagnosis based only on serology is not reliable in adults.